Euphorbia melanohydrata subsp. conica (Euphorbiaceae), a new subspecies from Namibia, with notes on the identification of similar medusoid euphorbias - Swanepoel, W. (Phytotaxa, 2012)
Euphorbia melanohydrata subsp. conica, here described as a new subspecies, is only known from a small area within the Gariep Centre of Endemism, southwestern Namibia. Diagnostic characters for subsp. conica include a distinctly conical or ovoid habit, a thickened main root usually without rhizomatous branches (plants not clump-forming), tuberculate lateral branches that often rebranch and persistent, stellate peduncles. A comparative table with diagnostic morphological features to distinguish between the two subspecies of E. melanohydrata and three other medusoid euphorbias (E. friedrichiae, E. multiceps and E. namibensis) is provided.